Temporal fluency and floor/ceiling scoring of intermediate and advanced speech on the ACTFL Spanish Oral Proficiency Interview–computer. (April 2023) - Cox, Troy L.; Brown, Alan V.; Thompson, Gregory L.
The rating of proficiency tests that use the Inter-agency Roundtable (ILR) and American Council on the Teaching of Foreign Languages (ACTFL) guidelines claims that each major level is based on hierarchal linguistic functions that require mastery of multidimensional traits in such a way that each level subsumes the levels beneath it. These characteristics are part of what is commonly referred to as floor and ceiling scoring. In this binary approach to scoring that differentiates between sustained performance and linguistic breakdown, raters evaluate many features including vocabulary use, grammatical accuracy, pronunciation, and pragmatics, yet there has been very little empirical validation on the practice of floor/ceiling scoring. This study examined the relationship between temporal oral fluency, prompt type, and proficiency level based on a data set comprised of 147 Oral Proficiency Interview - computer (OPIc) exam responses whose ratings ranged from Intermediate Low to Advanced High [AH]. As speakers progressed in proficiency, they were more fluent. In terms of floor and ceiling scoring, the prompts that elicited speech a level above the sustained level generally resulted in speech that was slower and had more breakdown than the floor-level prompts, though the differences were slight and not significantly different. Thus, temporal fluency features alone are insufficient in floor/ceiling scoring but are likely a contributing feature.